Hubungan Pengetahuan Remaja Putri Tentang Menstruasi Terhadap Perilaku Higienis Pada Saat Menstruasi - Syafrina Dewi Yanti; Agrina - -; Veny - Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This study aims to determine the reletionship between the knowledge of young women about menstruation and hygienic behavior during menstruation at SMA1 Benai, district of Benai, Kuantan Singingi. Number of samples is 70 people who were taken by using a random sampling technique. Instruments used in this study is a questionnaire with 24 statements. Results are analyzed using unvaried analysis and presented in a frequency distribution table. The result of this study indicates 55,0% of respondents have a high hygienic behavior at the time of menstruation. Respondents with a high knowledge of the 70 respondents who have menstruation hygienic behaviors positive in 22 (55.0%). Respondents with knowledge being the majority have hygienic behavior during menstruation positive in 6 (66.7%). Respondents with a majority having low knowledge on menstruation hygienic behaviors negatively by 12 (57.1%). Statistical analysis showed value P = 0.048 where P value < α (0.05) it can be concluded that there is a significant relationship between knowledge of the hygienic behavior during menstruation. Based on these results, it is suggested to the leaders and teaching staff of SMA 1 Benai to provide education about reproductive health and education about the importance of hygiene during menstruation, so that students will gain a comprehensive knowledge. Keywords : Knowledge, hygienic behavior during menstruation